A cerium oxide sulfur doped carbon aerogel micron microsphere and its preparation method and application
By loading cerium oxide on the surface of the carbon aerogel microspheres, cerium oxide-loaded sulfur-doped carbon aerogel microspheres were prepared, which solved the problem that the prior art was difficult to remove antimony in water contaminated with low concentrations of antimony, achieved efficient and selective antimony adsorption effect, and reduced the toxicity of antimony.
Patent Information
- Application Number
- CN202211482192.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-11-24
AI Technical Summary
The prior art is difficult to effectively remove antimony from low-concentration antimony contaminated water bodies, and the preparation process of adsorbents is complex and costly.
Cerium oxide-loaded sulfur-doped carbon aerogel microspheres are used as adsorption material, and cerium oxide is loaded on the surface of carbon aerogel microspheres through hydrothermal reaction to improve its adsorption performance on antimony.
It achieves rapid and efficient adsorption of antimony in water, has the advantages of good selectivity and large adsorption capacity, and can oxidize low-priced antimony into high-priced antimony, reducing its toxicity.
Smart Images

Figure CN115888651B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon aerogel microsphere, in particular to a cerium oxide loaded sulfur-doped carbon aerogel micron microsphere and a preparation method thereof, and to an application of the cerium oxide loaded sulfur-doped aerogel micron microsphere as an adsorption material in the restoration of antimony-contaminated water bodies, belonging to the technical field of heavy metal wastewater treatment. Background Art
[0002] Carbon materials are used in aerospace, electronics, materials, metallurgy, chemical industry and many other fields due to their rich structural features and functions. In the continuous research and application, many new carbon materials such as graphene, carbon microtubes, porous carbon materials and so on have emerged.
[0003] In recent years, surface modification of carbon materials and adding special functional groups to give carbon materials special properties have become a hot topic. Some polar functional groups on the surface of carbon materials can significantly improve the hydrophilicity of the materials, thereby achieving the purpose of applying carbon materials to heavy metal wastewater treatment. The radius of the sulfur atom in the thiol group is larger than that of the oxygen atom in the hydroxyl group, which is easier to polarize. Compared with the OH bond, the SH bond is easier to dissociate, more prone to oxidation, nucleophilic reactions, and has a stronger affinity for carbon atoms. At the same time, mercapto groups can also improve the adsorption capacity of carbon materials for heavy metal ions. For example, Kokalj et al. studied the binding of methyl, phenyl and mercapto substituted molecules to the copper surface. The results showed that mercapto substituted molecules are more likely to be adsorbed, deprotonated and bound than non-mercapto molecules (Kovacevic, N., Milosev, I., Kokalj, A. (2015) The roles of mercapto, benzene, and methyl groups in the corrosion inhibition of imidazoles on copper: II. Inhibitor-copper bonding. Corrosion Science 98, 457-470.); Xueying et al. Li et al. studied the adsorption performance of thiol-modified graphene materials for Cu(II), Pb(II) and Cd(II). The results showed that thiol-modified graphene materials have extremely high adsorption capacity for metal ions such as Cu(II), Pb(II) and Cd(II) (Li, XY, Zhou, HH, Wu, WQ, Wei, SD, Xu, Y., Kuang, YF (2015) Studies of heavy metal ion adsorption on Chitosan / Sulfydryl-functionalized graphene oxide composites. Journal of Colloid and Interface Science 448, 389-397.).
[0004] Cerium (Ce) is one of the most abundant and cheapest rare earth metals. It is a lanthanide element with two valence states (Ce(III) and Ce(IV)). It has been reported in the literature that the presence of cerium ions makes the adsorbent surface more positively charged, which will help attract anions such as arsenate, chromate, phosphate and fluoride (Z. Qi, TP Joshi, R. Liu, H. Liu, J. Qu, Synthesis of Ce(III)-doped Fe3O4 magnetic particles for efficacious removal of antibiotics from aqueous solution, J. Hazard. Mater. 329 (2017) 193–204.).
[0005] As a porous carbon material, carbon aerogel has attracted more and more attention in the fields of catalysis, adsorption separation and energy storage due to its high specific surface area, high porosity, stable chemical properties and good structural stability. The preparation of carbon aerogel microspheres generally requires three processes, namely sol-gel, drying and carbonization. The preparation process of carbon aerogel is becoming more and more mature, and improving its adsorption performance for pollutants by modifying carbon aerogel has become a hot research topic. The polymerization reaction of the m-diphenol-formaldehyde-sodium carbonate system is a suspension polymerization. The monomers easily form spherical droplets, and the reaction easily obtains gel microspheres with a spherical rate of 100% ("Gelation Mechanism of Carbon Aerogel Microspheres", Liu Ning et al., New Carbon Materials, 2009, 24(01):67-72.). Ou Shaotong et al. successfully prepared carbon aerogel microspheres by emulsion polymerization. The product is in the shape of regular spheres. The internal microstructure is composed of a large number of micron particles stacked together, containing a large number of pores, and Pd 2+ It has excellent adsorption capacity ("Study on the Synthesis Process Regulation and Adsorption Performance of Carbon Aerogel Microspheres", Ou Shaotong et al., Aging and Application of Synthetic Materials, 2013, 42(05): 6-9). Wen Shuangxi et al. prepared ternary defluorination adsorbent lanthanum-loaded magnetic carbon aerogel microspheres (MCAMs-La) by reverse emulsion polymerization, chemical coprecipitation and immersion in saturated lanthanum nitrate solution. The results showed that MCAMs-La has a fast defluorination speed and a large adsorption capacity, and is a defluorination adsorbent with great application prospects and value ("Preparation of Lanthanum-loaded Magnetic Carbon Aerogel Microspheres and Preliminary Study on Their Adsorption and Defluorination Effect", Wen Shuangxi et al., Journal of Guiyang University (Natural Science Edition), 2019, 14(02): 89-93).
[0006] Antimony is a toxic metal, and its toxicity varies with its valence state. The toxicity of trivalent antimony is ten times higher than that of pentavalent antimony. The existing conventional treatment methods can effectively remove high concentrations of antimony in water, but as people's requirements for water environment increase, conventional treatment methods can no longer meet the requirements of emission standards. Li Zhiping et al. prepared biopolymer iron-loaded (CS / CA-Fe). Under acidic conditions, CS / CA-Fe has an enrichment and adsorption effect on trace Sb(V) in water. The iron oxide in CS / CA-Fe has a complexing effect on Sb(V) and Sb(III), and can oxidize Sb(III) to Sb(V). CS / CA-Fe can treat trace antimony-containing wastewater in water, but some pollution will still be generated in the process of preparing the adsorbent ("Research on Enhanced Removal of Trace Antimony in Water by Biopolymer Iron-loaded Adsorbent", Li Zhiping, Suzhou University of Science and Technology, 2018). Kamberovic et al. adjusted the pH of metallurgical wastewater with a trivalent antimony concentration of 4.2 mg / L to 7, and then treated it with a large-pore cationic ion exchange resin containing gelatin aminodiacetic acid functional groups, successfully reducing the antimony concentration in the water to 0.5 mg / L ("Conceptual design for treatment of mining and metallurgical wastewaters which contains arsenic and antimony", Kamberovic Z J. Association of Metallurgical Engineers of Serbia, 2012, 18(4): 321-331.).
[0007] However, up to now, there is no technology for using carbon aerogel materials doped with sulfur and simultaneously loaded with cerium oxide to repair low-concentration antimony-contaminated water bodies. Summary of the invention
[0008] In view of the technical problems that common adsorbents in the prior art are difficult to remove low concentrations of antimony in heavy metal-contaminated wastewater, and the preparation process of the adsorbent is complicated and costly, the first object of the present invention is to provide a sulfur-doped carbon aerogel microsphere material with micron-sized, developed pore structure, large specific surface area, and surface-loaded cerium oxide, which has the advantages of fast and efficient adsorption of antimony in water, good selectivity, and large adsorption capacity, and can convert highly toxic low-valent antimony into high-valent antimony, and is suitable for the repair of antimony-contaminated water.
[0009] The second object of the present invention is to provide a method for preparing cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres, which is simple, low-cost and can be applied to large-scale production.
[0010] The third object of the present invention is to provide an application of cerium oxide loaded sulfur-doped carbon aerogel micron microspheres in the remediation of heavy metal contaminated wastewater. The cerium oxide loaded sulfur-doped carbon aerogel micron microsphere material can efficiently adsorb heavy metal antimony in water and oxidize low-valent antimony to achieve the purpose of water purification, especially for antimony in low-concentration antimony contaminated wastewater. It has the advantages of rapid and efficient adsorption, good selectivity, and large adsorption capacity, and can achieve the purpose of deep purification.
[0011] In order to achieve the above technical purpose, the present invention provides a cerium oxide loaded sulfur-doped carbon aerogel micron microsphere, which is composed of cerium oxide loaded on the surface and pores of the sulfur-doped carbon aerogel micron microsphere.
[0012] The cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres of the present invention use carbon aerogel micron microspheres as a matrix, have a size of micrometer level, and have a well-developed pore structure, a large specific surface area, and a strong physical adsorption capacity. The cerium oxide is loaded while sulfur is uniformly doped, and the two have a synergistic effect on the adsorption of antimony in water. Sulfur has a coordination adsorption effect on antimony, and cerium oxide has a high selective electrostatic adsorption of antimony in the form of anions. The synergistic effect of various adsorptions gives it the advantages of rapid and efficient adsorption, good selectivity, large adsorption capacity, and the like.
[0013] As a preferred solution, the particle size of the cerium oxide-loaded sulfur-doped carbon aerogel microspheres is distributed in the range of 50 to 1000 nm, and the specific surface area is in the range of 200 to 700 m 2 / g, pore volume is 0.25cm 3 / g~0.45cm 3 / g, the mass percentage of sulfur is 0.6% to 0.9%, and the mass percentage of cerium is 4 to 8%. The further preferred specific surface area is 300 to 400 m 2 / g, and the particle size distribution is between 400 and 800 nm.
[0014] The invention provides a method for preparing cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres. The preparation method comprises the following steps: mixing an aqueous phase containing phenolic monomers, thiocyanate, aldehyde monomers and a catalyst with an oil phase containing a surfactant, and then carrying out a polymerization reaction under stirring; after the polymerization reaction is completed, carrying out solid-liquid separation, drying and carbonization treatment to obtain the sulfur-doped carbon aerogel micron microspheres; and carrying out a hydrothermal reaction between the sulfur-doped carbon aerogel micron microspheres and an alkaline solution containing a cerium salt, and then carrying out solid-liquid separation, washing and drying in sequence to obtain the cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres.
[0015] The technical solution of the present invention adopts thiocyanuric acid as a modifier. By introducing thiocyanuric acid during the polymerization reaction, it can be uniformly doped in situ in the gel micron microspheres. After high-temperature pyrolysis, a large number of sulfur-containing groups can be generated on the surface of the carbon aerogel micron microspheres. At the same time, some sulfur-containing groups are retained in the internal spatial structure of the carbon aerogel microspheres. These sulfur-containing groups constitute the adsorption active sites of heavy metal antimony. The sulfur atoms volatilized and removed during the carbonization process leave marks on the surface and inside of the carbon aerogel microspheres, which can also improve the adsorption performance of the sulfur-doped carbon aerogel microspheres.
[0016] The technical solution of the present invention adopts a hydrothermal synthesis method to load cerium oxide on the surface of sulfur-doped carbon aerogel. The hydrothermal synthesis method can make cerium oxide more evenly distributed on the surface of carbon aerogel microspheres. Based on a large amount of cerium oxide loading, a large number of hydroxyl groups are formed on the surface of carbon aerogel microspheres. The hydroxyl groups can be replaced by anions. The polar functional groups can increase the hydrophilicity of the surface of carbon aerogel microspheres, and at the same time make the adsorbent surface positively charged, which helps to attract anions. Therefore, the doping of cerium oxide can improve the adsorption performance of carbon aerogel microspheres for heavy metal antimony. At the same time, cerium oxide can be used as an oxidant to oxidize low-valent and highly toxic heavy metal antimony into a low-toxic high-valent state.
[0017] As a preferred solution, the phenolic monomer includes at least one of phenol, catechol and resorcinol. These phenolic monomers are common raw materials for phenolic resins, and the selection range of the phenolic monomers of the present invention is not limited to the above-mentioned ones.
[0018] As a preferred solution, the aldehyde monomer includes at least one of formaldehyde and furfural; these aldehyde monomers are common raw materials for phenolic resins. The selection range of the aldehyde monomers of the present invention is not limited to the above-mentioned ones.
[0019] As a preferred solution, the mass ratio of the phenolic monomer to the aldehyde monomer is 10:1 to 1:10. The mass ratio of the phenolic monomer to the aldehyde monomer is further preferably 3:1 to 1:3. The preferred ratio range can obtain gel microspheres with higher crosslinking strength.
[0020] As a preferred solution, the mass ratio of the thiocyanuric acid to the aldehyde monomer is 8:1 to 1:8. More preferably, it is 1:1 to 1:4. As the amount of thiocyanuric acid doping increases, the sulfur content of the carbon aerogel microspheres can be increased, but too high a doping amount of thiocyanuric acid will affect the formation of the carbon aerogel microspheres.
[0021] As a preferred solution, the catalyst includes sodium carbonate, which is a very common catalyst in the synthesis of phenolic resins. As a more preferred solution, the catalyst is 0.5-2% of the mass of the phenolic monomer.
[0022] As a preferred solution, the total mass percentage of phenolic monomers, thiocyanuric acid, aldehyde monomers and catalysts in the aqueous phase is 1-60%, and the total mass percentage of phenolic monomers, thiocyanuric acid, aldehyde monomers and catalysts in the aqueous phase is more preferably 30-60%.
[0023] As a preferred solution, the oil phase contains at least one water-insoluble solvent selected from cyclohexane, petroleum ether or peanut oil.
[0024] As a preferred solution, the surfactant includes span60 and / or span80.
[0025] As a preferred solution, the surfactant accounts for 5-50% of the mass of the oil phase. More preferably, the surfactant accounts for 8-13% of the mass of the oil phase. The preferred amount of surfactant is conducive to the formation of micron-sized gel microspheres.
[0026] As a preferred solution, the volume ratio of the water phase to the oil phase is O / A=10:1 to 1:10. The volume ratio of the water phase to the oil phase is more preferably 5:1 to 1:1.
[0027] As a preferred solution, the conditions of the polymerization reaction are: first react at room temperature for 1 to 30 minutes at a stirring rate of 300 to 1500 r / min, and then react at a temperature of 40 to 90°C for 6 to 36 hours at a stirring rate of 50 to 600 r / min. During the polymerization reaction, the size of the gel microspheres can be regulated by controlling the stirring rate, temperature and the amount of surfactant. In the early stage of the polymerization reaction, a lower temperature and a higher stirring rate are controlled, and a larger mechanical shear force is used and the dispersion effect of the surfactant is used to make the polymerized monomers form uniform micro-emulsion droplets with micron level, and the monomers in the micro-emulsion droplets are initially polymerized to form gel microspheres. In the middle and late stages of the polymerization reaction, the stirring rate is slowed down and the temperature is increased, mainly to further carry out the polymerization reaction to increase the internal crosslinking of the gel microspheres, so that the gel microspheres gradually form a three-dimensional network structure, generate a large number of pore structures, and greatly improve the stability of the gel microspheres. Therefore, the formed gel microspheres have good stability, can be conventionally dried, and after high-temperature carbonization, the crosslinked skeleton structure can still be maintained and a large number of micropores are retained. Further preferred polymerization reaction conditions are: first react at room temperature for 5 to 15 minutes under stirring conditions of 600 to 1200 r / min, and then react at 40 to 70°C for 12 to 42 hours under stirring conditions of 300 to 600 r / min. Under the preferred reaction conditions, the early stage is conducive to the formation of micron-level gel microspheres, and the later stage is conducive to promoting the cross-linking reaction inside the microspheres to form a three-dimensional network structure, and then it can be directly dried at room temperature.
[0028] As a preferred solution, the carbonization treatment conditions are: in a protective atmosphere, at a temperature of 300 to 1200°C, and keep warm for 1 to 24 hours. The protective atmosphere is generally an inert atmosphere, and an inert atmosphere such as nitrogen or argon can be selected. Further preferred carbonization conditions are: in a protective atmosphere, at a temperature of 600 to 900°C, and keep warm for 3 to 6 hours. A large number of experiments have shown that the higher the carbonization temperature, the more micropores are produced, but too high a temperature will cause the three-dimensional network structure to collapse, and too high a temperature will lead to an increase in the amount of sulfur removed, so the optimal carbonization temperature is 600 to 900°C.
[0029] As a preferred solution, the hydrothermal reaction conditions are: the reaction temperature is 50-70° C. and the reaction time is 12-36 hours. The preferred hydrothermal reaction conditions are conducive to promoting the formation and in-situ deposition of cerium oxide and increasing the loading rate of cerium oxide.
[0030] As a preferred solution, the mass ratio of the sulfur-doped carbon aerogel microspheres to the cerium salt is 1:1 to 1:5. The mass ratio of the sulfur-doped carbon aerogel microspheres to the cerium salt is further preferably 1:1 to 1:3. The cerium salt can be a common water-soluble cerium salt in the prior art, such as CeCl3·7H2O.
[0031] As a preferred solution, the pH of the alkaline solution containing the cerium salt is greater than 7 and less than or equal to 10.
[0032] As a preferred solution, the solid product (wet gel microspheres) obtained by the solid-liquid separation can be obtained by freeze drying, vacuum drying, supercritical drying, room temperature drying, etc. to obtain dry gel microspheres. Since the gel microspheres prepared in the present invention have a strong three-dimensional structure, dry gel microspheres can be directly obtained by room temperature drying.
[0033] As a preferred solution, a small amount of sodium carbonate is added to the aqueous phase to adjust the system to a weakly alkaline environment.
[0034] The invention also provides cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres, which are obtained by the preparation method.
[0035] The present invention also provides an application of cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres, which are used as adsorption materials for the restoration of antimony-contaminated water bodies.
[0036] As a preferred solution, the ratio of cerium oxide-loaded sulfur-doped carbon aerogel microspheres added to the antimony-contaminated water is not higher than 2 g / L. It is more preferably 0.05 to 1.5 g / L, and further preferably 0.5 to 1 g / L. The concentration of antimony in the antimony-contaminated water is preferably 25 mg / L to 100 mg / L.
[0037] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0038] 1) The preparation process of the cerium oxide-loaded sulfur-doped carbon aerogel microspheres provided by the present invention is simple, the reaction conditions are mild, no harmful waste is generated, the operation is highly repeatable, and it is conducive to large-scale production.
[0039] 2) The cerium oxide-loaded sulfur-doped carbon aerogel microspheres provided by the present invention have a well-developed pore structure and a large specific surface area, and are loaded with cerium oxide and doped with sulfur, and the two exhibit a synergistic adsorption effect on the adsorption of heavy metal antimony. They have a high adsorption capacity and a strong adsorption ability for heavy metal antimony, and have good adsorption performance for antimony in low-concentration heavy metal antimony-contaminated wastewater. At the same time, they can oxidize trivalent antimony to pentavalent antimony, thereby reducing the toxicity of heavy metal antimony.
[0040] 3) The cerium oxide-loaded sulfur-doped carbon aerogel microspheres provided by the present invention are simple to use and can be directly added to antimony-contaminated wastewater for use, and the added amount is small, the antimony adsorption effect is significant, and it also has the potential to passivate heavy metal antimony pollution in the soil. BRIEF DESCRIPTION OF THE DRAWINGS
[0041]
Figure 1
[0042]
Figure 2
[0043]
Figure 3
[0044]
Figure 4
[0045]
Figure 5
[0046]
Figure 6
Figure 7
[0047] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0048] Comparative Example 1
[0049] In a 250 mL single-necked bottle, add 7.78 g of resorcinol and 11.48 g of formaldehyde solution (37 wt %), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, add 2.0g thiocyanate, and then pour in a mixture consisting of 108ml peanut oil and 12ml span80, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react at a reaction temperature of 60°C for 24h. After the reaction is completed, reddish-brown solid particles are present, and reddish-brown solids are obtained by centrifugation, which are sulfur-doped dry gel micron microspheres. After drying at normal pressure, they are heated at 900°C for 2h in a tubular furnace under a nitrogen atmosphere. After cooling, the black solid is taken out to obtain sulfur-doped carbon aerogel micron microspheres. The sulfur content of the carbon aerogel is 0.686%, the average particle size is 782.9nm, and the specific surface area is 352.87m 2 / g, average pore diameter 2.89nm, pore volume 0.25cm 3 / g.
[0050] Example 1
[0051] In a 250 mL single-necked bottle, add 7.78 g of resorcinol and 11.48 g of formaldehyde solution (37 wt%), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, add 2.0g thiocyanate, and then pour in a mixture consisting of 108ml peanut oil and 12ml span80, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react at a reaction temperature of 60℃ for 24h. After the reaction is completed, red-brown solid particles appear, and red-brown solids are obtained by centrifugation. After drying at normal pressure, they are heated at 900℃ in a tubular furnace under a nitrogen atmosphere for 2h. After cooling, the black solid is taken out to obtain sulfur-doped carbon aerogel micron microspheres. 0.5g CeCl3·7H2O is added to 50ml deionized water, dissolved, and then ammonia (28 wt %), adjusting the pH value of the solution to 8, adding 0.5 g of sulfur-doped carbon aerogel microspheres, pouring the mixed solution into a reactor, stirring at a stirring rate of 200 r / min for 24 h, controlling the reaction temperature at 60 ° C. After the reaction is completed, filtering and drying are performed to obtain cerium oxide-loaded sulfur-doped carbon aerogel microspheres. The carbon aerogel has a cerium content of 7.22%, an average particle size of 610.5 nm, and a specific surface area of 294.51 m 2 / g, average pore diameter 3.22nm, pore volume 0.237cm 3 / g.
[0052] Comparative Example 2
[0053] In a 250 mL single-necked bottle, add 7.78 g of resorcinol and 11.48 g of formaldehyde solution (37 wt %), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, add 2.0g thiocyanate, and then pour in a mixture consisting of 108ml peanut oil and 12ml span80, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react at a reaction temperature of 60°C for 24h. After the reaction is completed, reddish-brown solid particles are present, and reddish-brown solids are obtained by centrifugation. After drying at normal pressure, they are heated at 700°C in a tubular furnace under a nitrogen atmosphere for 2h. After cooling, the black solid is taken out to obtain sulfur-doped carbon aerogel micron microspheres. The sulfur content of the carbon aerogel is 0.807%, the average particle size is 725.6nm, and the specific surface area is 269.47m 2 / g, average pore diameter 2.86nm, pore volume 0.19cm 3 / g.
[0054] Example 2
[0055] In a 250 mL single-necked bottle, add 7.78 g of resorcinol and 11.48 g of formaldehyde solution (37wt %), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, add 2.0g thiocyanate, and then pour in a mixture consisting of 108ml peanut oil and 12ml span80, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react at a reaction temperature of 60℃ for 24h. After the reaction is completed, red-brown solid particles appear, and red-brown solids are obtained by centrifugation. After drying at normal pressure, they are heated at 700℃ in a tubular furnace under a nitrogen atmosphere for 2h. After cooling, the black solid is taken out to obtain sulfur-doped carbon aerogel microspheres. 0.5g CeCl3·7H2O is added to 50ml deionized water, dissolved, and then ammonia (28 wt %), adjusting the pH value of the solution to 8, adding 0.5 g of sulfur-doped carbon aerogel microspheres, pouring the mixed solution into a reactor, stirring at a stirring rate of 200 r / min for 24 h, controlling the reaction temperature at 60 ° C. After the reaction is completed, filtering and drying are performed to obtain cerium oxide-loaded sulfur-doped carbon aerogel microspheres. The carbon aerogel has a cerium content of 6.85%, an average particle size of 436.4 nm, and a specific surface area of 218.51 m 2 / g, average pore diameter 3.32nm, pore volume 0.19cm 3 / g.
[0056] Example 3
[0057] The sulfur-doped carbon aerogel microspheres prepared in Comparative Example 1 and Example 1 and the sulfur-doped carbon aerogel microspheres loaded with cerium oxide were used as adsorbents, respectively, and trivalent antimony heavy metal solutions with different concentration gradients (concentrations ranging from 25 to 400 ppm, antimony in the form of SbO3 3- In the form of, sulfur-doped carbon aerogel microspheres and cerium oxide-loaded sulfur-doped carbon aerogel microspheres were added in an amount of 1 g / L, and adsorbed for 300 min at 25 ° C and 250 r / min. The water samples after adsorption were analyzed. The saturated adsorption capacity of the sulfur-doped carbon aerogel microspheres synthesized in Comparative Example 1 was 295.18 mg / g, and the saturated adsorption capacity of the cerium oxide-loaded sulfur-doped carbon aerogel microspheres synthesized in Example 1 was 424.83 mg / g.
[0058] Example 4
[0059] The sulfur-doped carbon aerogel nanospheres prepared in Comparative Example 1 and Example 1 and the sulfur-doped carbon aerogel nanospheres loaded with cerium oxide were used as adsorbents, respectively, and 50 mg / L of trivalent antimony heavy metal solution (antimony in the form of SbO3 3-The results show that the adsorption efficiency of the sulfur-doped carbon aerogel nanospheres synthesized in Comparative Example 1 is 31.62%, 45.17%, 58.53%, 75.68% and 92.14% at 5min, 30min, 60min, 180min and 300min, respectively. The adsorption efficiency of the cerium oxide-loaded sulfur-doped carbon aerogel nanospheres synthesized in Example 1 is 83.41%, 88.72%, 90.15%, 93.51% and 96.19% at 5min, 30min, 60min, 180min and 300min, respectively.
[0060] Example 5
[0061] In a 250 mL single-necked bottle, add 5.44 g of resorcinol and 11.48 g of formaldehyde solution (37 wt %), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, add 2.0g thiocyanate, and then pour in a mixture consisting of 108ml peanut oil and 12ml span80, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react at a reaction temperature of 60℃ for 24h. After the reaction is completed, red-brown solid particles appear, and red-brown solids are obtained by centrifugation. After drying at normal pressure, they are heated at 900℃ in a tubular furnace under a nitrogen atmosphere for 2h. After cooling, the black solid is taken out to obtain sulfur-doped carbon aerogel micron microspheres. 0.9g CeCl3·7H2O is added to 50ml deionized water, dissolved, and then ammonia (28 wt %), adjusting the pH value of the solution to 8, adding 0.3 g of sulfur-doped carbon aerogel microspheres, pouring the mixed solution into a reactor, stirring at a stirring rate of 200 r / min for 24 h, controlling the reaction temperature at 60° C., filtering and drying after the reaction, and obtaining cerium oxide-loaded sulfur-doped carbon aerogel microspheres. The carbon aerogel has a cerium content of 9.65%, an average particle size of 756.2 nm, and a specific surface area of 188.33 m 2 / g, average pore diameter 4.10nm, pore volume 0.193cm 3 / g.
[0062] Comparative Example 3
[0063] In a 250 mL single-necked bottle, add 7.78 g of resorcinol and 11.48 g of formaldehyde solution (37 wt%), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, add 2.0g thiocyanate, then pour in 108ml peanut oil and 12ml span80 to form a mixture, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react at a reaction temperature of 60℃ for 24h. After the reaction is completed, red-brown solid particles appear, and red-brown solids are obtained by centrifugation. After drying at normal pressure, they are heated at 700℃ in a tubular furnace under a nitrogen atmosphere for 2h. After cooling, the black solid is taken out to obtain sulfur-doped carbon aerogel micron microspheres. 0.2g CeCl3·7H2O is added to 50ml deionized water, dissolved, and then ammonia (28 wt %), adjusting the pH value of the solution to 8, adding 0.6 g of sulfur-doped carbon aerogel microspheres, pouring the mixed solution into a reactor, stirring at a stirring rate of 200 r / min for 24 h, controlling the reaction temperature at 60° C., filtering and drying after the reaction, and obtaining cerium oxide-loaded sulfur-doped carbon aerogel microspheres. The carbon aerogel has a cerium content of 4.12%, an average particle size of 512.3 nm, and a specific surface area of 189.39 m 2 / g, average pore diameter 3.07nm, pore volume 0.15cm 3 / g.
[0064] Comparative Example 4
[0065] In a 250 mL single-necked bottle, add 7.78 g of resorcinol and 11.48 g of formaldehyde solution (37 wt %), 0.075g sodium carbonate, add 19.8g deionized water, stir evenly, then pour in a mixture consisting of 108ml peanut oil and 12ml span80, stir at a stirring rate of 1000r / min for 10min to form an emulsion, adjust the stirring rate to 400r / min, start heating, and when the reaction reaches the set temperature, start timing, and react for 24h at a reaction temperature of 60°C. After the reaction is completed, reddish-brown solid particles are present, and reddish-brown solids are obtained by centrifugation. After drying at normal pressure, they are heated at 900°C in a tubular furnace for 2h under a nitrogen atmosphere. After cooling, the black solid is taken out to obtain carbon aerogel micron microspheres. The average particle size of the carbon aerogel microspheres is 512nm, and the specific surface area is 460m 2 / g, average pore diameter 2.265nm, pore volume 0.324cm 3 / g.
[0066] Example 6
[0067] The carbon aerogel nanospheres prepared in Comparative Example 1, Comparative Example 2, Example 1 and Example 5 were used as adsorption materials, and trivalent antimony heavy metal solution (antimony in the form of SbO33- The carbon aerogel nanospheres were used for adsorption experiments at 25°C and 250 r / min. The water sample analysis after adsorption is shown in the following table:
[0068]
[0069]
Claims
1. A method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres, characterized in that: After mixing an aqueous phase containing phenolic monomers, trithiocyanate, aldehyde monomers and a catalyst with an oil phase containing a surfactant, a polymerization reaction is carried out under stirring. After the polymerization reaction is completed, solid-liquid separation, drying and carbonization treatment are carried out to obtain sulfur-doped carbon aerogel micron microspheres; after hydrothermal reaction of the sulfur-doped carbon aerogel micron microspheres with an alkaline solution containing a cerium salt, solid-liquid separation, washing and drying are carried out in sequence to obtain cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres; The cerium oxide-loaded sulfur-doped carbon aerogel micron microspheres are composed of cerium oxide loaded on the surface and pores of the sulfur-doped carbon aerogel micron microspheres.
2. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1, characterized in that: The particle size of the cerium oxide-loaded sulfur-doped carbon aerogel microspheres is distributed in the range of 50-1000 nm, and the specific surface area is in the range of 200-700 m 2 / g, pore volume is 0.25cm 3 / g~0.45cm 3 / g, the mass percentage of sulfur is 0.6%~0.9%, and the mass percentage of cerium is 4~8%.
3. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1, characterized in that: The phenolic monomer includes at least one of phenol, catechol and resorcinol; The aldehyde monomer includes at least one of formaldehyde and furfural; The catalyst includes sodium carbonate; The mass ratio of the phenolic monomer to the aldehyde monomer is 10:1 to 1:10; The mass ratio of the thiocyanuric acid to the aldehyde monomer is 8:1 to 1:8; The catalyst accounts for 0.5-2% of the mass of the phenolic monomer.
4. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1 or 3, characterized in that: The total mass percentage content of phenol monomers, thiocyanuric acid, aldehyde monomers and catalysts in the water phase is 1-60%.
5. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1, characterized in that: The oil phase contains at least one water-insoluble solvent selected from cyclohexane, petroleum ether or peanut oil; The surfactant includes span60 and / or span80; The mass of the surfactant accounts for 5% to 50% of the mass of the oil phase.
6. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1 or 5, characterized in that: The volume ratio of the water phase to the oil phase is O / A=10:1~1:
10.
7. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1, characterized in that: The polymerization reaction conditions are: first, at a stirring rate of 300-1500 r / min, react at room temperature for 1-30 min, then at a stirring rate of 50-600 r / min, react at a temperature of 40-90° C. for 6-36 h; The carbonization treatment conditions are: in a protective atmosphere, at a temperature of 300-1200° C., and keeping warm for 1-24 hours.
8. The method for preparing cerium oxide-loaded sulfur-doped carbon aerogel microspheres according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: reacting at a temperature of 50-70° C. for 12-36 hours; The mass ratio of the sulfur-doped carbon aerogel microspheres to the cerium salt is 1:1 to 1:5; The pH of the alkaline solution containing the cerium salt is greater than 7 and less than or equal to 10.
Citation Information
Patent Citations
Carbon-sulfur composite positive electrode, and preparation method and application thereof
CN109599539A
Purification method and purifier of radioactive contaminated water or industrial waste water, and volume reduction method
JP2014213233A